Beyond scholarships: Perceptions of inclusion and academic support among Peruvian higher education participants - Huamanttupa Mar, Willian (2026)
The existence of inclusion and academic support policies at universities supports the idea of an education that is available and equitable to all students; however, there are barriers and facilitators that influence the academic and social experience of Peruvian university students. The objective of this study was to analyze the perceptions of low-income students regarding the inclusion and academic support activities implemented at a Peruvian university. The qualitative-phenomenological method allowed us to analyze the perceptions of 20 university students from a private university in Juliaca, Peru, during the 2024 academic year. Through semi-structured interviews and a semi-pragmatic analysis based on Peirce's theory, three dimensions were explored: structural limitations in scholarship policies, pedagogical gaps in academic support, and dynamics of social exclusion. The results demonstrated that scholarships are essential for student retention, but challenges persist in complex administrative processes and effective communication. Academic reinforcement programs were valued, but there is a need to personalize them and extend them throughout the entire academic program. Although inclusion strategies strengthen a sense of belonging and academic performance, they must be adapted to individual needs. The conclusions highlight the importance of reevaluating inclusion policies and actions with a rights-based approach, combining academic and financial support with mentoring and community awareness. The study provides empirical evidence for reformulating educational policies in Peru regarding vulnerable student communities and suggests urgently addressing socioeconomic inequalities in higher education.